2019
DOI: 10.1101/684001
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

FMRFGene Expression in the Nervous System of the SquidDoryteuthis Pealei* Hatchling

Abstract: FMRFamide is a neuropeptide that is widely distributed in invertebrates and known to be involved in many physiological functions. Previously we noted marked differences in expression of the fmrf gene in the stellate ganglion of Doryteuthis pealei* compared to the central nervous system. In this study we aimed to examen the brain systems of Doryteuthis pealei* for the presence and distribution of fmrfexpressing cells and fiber networks. Late squid embryos and hatchlings were examined by in situ hybridization an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…We could identify known cell types in the dataset such as dopaminergic (DOP), GABAergic (GABA), serotonergic (SERT) and peptidergic (PEP-fmrfa+) neuronal subtypes. A large body of work has been done on the localization of FMRFamide (fmrfa) synthesizing neurons in different cephalopods 17,[36][37][38][39] . In this study, we identified three different fmrfa precursor genes which are differentially expressed between cell types (Fig.…”
Section: Cluster Annotation Based On Neurotransmitter and Peptide Exp...mentioning
confidence: 99%
“…We could identify known cell types in the dataset such as dopaminergic (DOP), GABAergic (GABA), serotonergic (SERT) and peptidergic (PEP-fmrfa+) neuronal subtypes. A large body of work has been done on the localization of FMRFamide (fmrfa) synthesizing neurons in different cephalopods 17,[36][37][38][39] . In this study, we identified three different fmrfa precursor genes which are differentially expressed between cell types (Fig.…”
Section: Cluster Annotation Based On Neurotransmitter and Peptide Exp...mentioning
confidence: 99%
“…In cephalopods, the study of the molecular machinery occurring in these processes is still limited. Few studies of cuttlefish ( Agin et al, 2000 , 2001 , 2003 ; Focareta et al, 2014 ; Focareta and Cole, 2016 ; Bian et al, 2018 ), squid ( Giuditta et al, 2002 ; Kimbell and McFall-Ngai, 2003 ; Burbach et al, 2019 ), and octopus ( Zarrella, 2011 ; Zarrella et al, 2015 ; van Giesen et al, 2020 ; see also Prado-Álvarez et al, 2022 ) have been based on an exiguous number of specific candidate molecules involved in given functions or biological aspects of cephalopod plasticity.…”
Section: Discussionmentioning
confidence: 99%